Isolation and Purification of Two Triterpenoids from the Chinese Medicinal Plant Fomes officinalis ames - Zhang, Huifeng; Feng, Bo; Liu, Ke; Guo, Shuying (Asian Journal of Chemistry, 2013)
A high-speed counter-current chromatography method is developed for the separation and purification of two triterpenoids from the Chinese Uyghur medicinal plant Fomes officinalis ames. Crude triterpenoids were obtained from Fomes officinalis ames through ethanol extraction. Preparative high-speed counter-current chromatography with two-phase solvent systems made up of n-hexane-ethylacetate-methanol-water with a volume ratio of 1:1.5:1.2:1 (v/v) was successfully performed in a stepwise elution. The process yielded two relatively pure triterpenoids in a single run from 500 mg crude extract. The purities of the dehydrosulphurenic acid and 3-keto-dehydrosulphurenic acid were 96.8 % and 92.3 %, respectively.